2016
DOI: 10.1093/jnci/djv392
|View full text |Cite
|
Sign up to set email alerts
|

An Ethical Framework for Allocating Scarce Life-Saving Chemotherapy and Supportive Care Drugs for Childhood Cancer

Abstract: Shortages of life-saving chemotherapy and supportive care agents for children with cancer are frequent. These shortages directly affect patients' lives, compromise both standard of care therapies and clinical research, and create substantial ethical challenges. Efforts to prevent drug shortages have yet to gain traction, and existing prioritization frameworks lack concrete guidance clinicians need when faced with difficult prioritization decisions among equally deserving children with cancer. The ethical frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Recently, Unguru et al have published an ethical framework to better deal with this menace. [36] The Ecuadorian Ministry of Health has recently updated a list of drug shortages where generic and old drugs as cyclophosphamide, cytarabine, chlorambucil, melphalan and leucovorine were no longer (or poorly) available since 2011, thus pushing oncologists to prescribe newer and more expensive drugs. Whether this is the result of planned shortages of good and less costly oncologic drugs by companies or of complexities in public procurement is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Unguru et al have published an ethical framework to better deal with this menace. [36] The Ecuadorian Ministry of Health has recently updated a list of drug shortages where generic and old drugs as cyclophosphamide, cytarabine, chlorambucil, melphalan and leucovorine were no longer (or poorly) available since 2011, thus pushing oncologists to prescribe newer and more expensive drugs. Whether this is the result of planned shortages of good and less costly oncologic drugs by companies or of complexities in public procurement is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Varying utility‐oriented and rights‐oriented conceptualizations of distributive justice are at the heart of ongoing tensions surrounding SMA treatment decisions. With nusinersen approved for use in Canada, and several other SMA therapeutics expected to be approved in the near future, as well as thousands of therapeutic pipelines in progress for other diseases, a principle‐based ethics framework to guide decision‐making that acknowledges the instrumental and potentially normative application of economic algorithms and reflective of public engagement could be a mechanism for pursuing the transparent and equitable allocation of health‐care resources …”
Section: Ethical Considerations Of Nusinersen Therapy For the Treatmementioning
confidence: 99%
“…Ethical concerns of medication shortages have been examined via bioethical frameworks and empirical studies; they also should be considered within trainee shortage management. 19,24 Both ethical theory and data on patient preference suggested that patients should, and want to, be told of shortages. 22,24 Arguments against patients being informed are due to the lack of alternatives, because clinicians regard substitution differences as insubstantial, or because clinicians think that patients will be unnecessarily concerned.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Prior studies have investigated the etiologies of shortages, mitigation mechanisms, the impact of specific shortages on patient outcomes, and the merits of different ethical allocation frameworks. 1,10,[13][14][15][16][17][18][19] A recent survey of US hospital-based pharmacists found that medication rationing episodes were common, decisions were often made without outside input, and patients were infrequently informed. 4 These findings raise ethical concerns over transparency, clinician decision-making and moral distress, and the accepted standard of shared decision-making.…”
Section: Introductionmentioning
confidence: 99%